Capital-Labor Conflict and the Productivity Slowdown - Gordon, David M. (American Economic Review, 1981)
The slowdown in productivity growth during the 1970's continues to puzzle neoclassical economists. As Edward Denison concludes, what happened is, to be blunt, a mystery(p. 4). This mystification should not seem particularly surprising, since neoclassical economists pay so little attention to the operations of the process of production. In contrast, Marxist economists have recently placed high priority on analyses of production relations in capitalist economies (see Herbert Gintis; and Michael Reich and James Devine). Although not yet applied to studies of aggregate labor productivity, this work should nonetheless provide fruitful guidelines for Marxian investigations of the productivity slowdown. Among other suggestions, the recent literature emphasizes the importance of both external and internal mechanisms of labor Where would these clues guide our initial explorations of the productivity puzzle? The external effect seems clearly to point in the wrong direction. Labor markets have become relatively looser during the 1970's. This heightened labor market competition ought to have pushed workers harder and, other things equal, to have increased labor productivity. In contrast, the clues about internal control mechanisms seem more promising. Many corporations have been complaining about worker performance, while both absenteeism and worker dissatisfaction have been rising (see Graham Staines). Pursuing these clues, I develop and empirically test in this paper a formal Marxian model of aggregate labor productivity which pays special attention to both the emergence and erosion in the postwar U.S. economy of a vast internal corporate apparatus of control. (See Richard C. Edwards for definition and elaboration.) The analysis is very provisional, but the results reported here nonetheless provide strong support for a single central conclusion: The declining effectiveness of the postwar system of bureaucratic control appears to explain almost all of the recent slowdown in productivity growth. Viewed from the Marxian perspective, the productivity slowdown seems no more mysterious than any other contradiction of capitalist economies.